2014
DOI: 10.1371/journal.pone.0098435
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ARNT (Aryl Hydrocarbon Receptor Nuclear Translocator) in β-Cells Causes Islet Transplant Failure with Impaired β-Cell Function

Abstract: BackgroundReplacing β-cells by islet-transplantation can cure type 1 diabetes, but up to 70% of β-cells die within 10 days of transplantation. ARNT (Aryl hydrocarbon Receptor Nuclear Translocator) regulates β-cell function, and potentially survival. Lack of ARNT impairs the ability of β-cells to respond to physiological stress and potentiates the onset of diabetes, but the exact role of ARNT in graft outcome is unknown.AimTo investigate the effect of β-cell deletion of ARNT on graft outcomes.MethodsIslets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Selective deletion of ARNT in beta cell of the pancreas leads to glucose intolerance, impaired insulin secretion and deregulated islet gene expression [6,7]. Other studies using conditional knockout mice have additionally reported the critical role of pancreatic ARNT in beta cell transplant, and glucose tolerance during pregnancy [8,9]. ARNT expression is also repressed in diabetic livers.…”
Section: Introductionmentioning
confidence: 99%
“…Selective deletion of ARNT in beta cell of the pancreas leads to glucose intolerance, impaired insulin secretion and deregulated islet gene expression [6,7]. Other studies using conditional knockout mice have additionally reported the critical role of pancreatic ARNT in beta cell transplant, and glucose tolerance during pregnancy [8,9]. ARNT expression is also repressed in diabetic livers.…”
Section: Introductionmentioning
confidence: 99%
“…Mice that had random-fed BGLs of ≥ 20mmol/l (360mg/dl) on 2 separate occasions were considered diabetic. Intraperitoneal glucose tolerance tests (GTT, 2g/kg) were performed in mice fasted for 4 hours, as previously described ( Lalwani et al, 2014 ; Stokes et al, 2013 ; Scott et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse islets were isolated and purified from uninfected and CV infected 8-week-old male FC and βHIF-1α mice as described previously ( Cheng et al, 2010 ; Gunton et al, 2005 ; Lalwani et al, 2014 ; Stokes et al, 2013 ). The pancreas was distended with 3mls of liberase containing solution, and incubated at 37°C for 16.5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Osteocalcin which is produced by osteoblasts has recently come to a new light for its role in regulating beta-cell function [75]. Its classic use is as a marker of bone formation.…”
Section: Potential Bone To Muscle Vitamin D Cross-talkmentioning
confidence: 99%
“…It is regulated by vitamin D and its gene contains a vitamin D response element (VDRE) indicating direct regulation by vitamin D [2]. It has potential effects in muscle, in which it alters mitochondrial function, insulin sensitivity [75], and possibly strength in women.…”
Section: Potential Bone To Muscle Vitamin D Cross-talkmentioning
confidence: 99%